Deno Web Development write, test, maintain and deploy javascript and typescript web... applications using deno. - Santos, Alexandre Portela dos (PACKT PUBLISHING LIMITED, 2021)
Deno Web Development is the definitive guide to starting to write, test, and deploy reliable Deno applications. You'll be able to apply Deno to common use cases from simple command-line interface (CLI) utilities to multi-featured APIs. By the end of this Deno book, you'll be comfortable with using Deno for real-world web application development.